The sensitivity of an anatomical coordinate system to anatomical variation and its effect on the description of knee kinematics as obtained from dynamic CT imaging. (April 2022) - Dunning, H.; van de Groes, S.A.W.; Verdonschot, N.; Buckens, C.F.; Janssen, D.
Highlights: Dynamic CT imaging provides insight into underlying cause of knee disorders Description of knee kinematics is influenced by anatomy and pathology Statistical Shape Modeling is useful to discriminate between anatomy and pathology Influence of anatomy on kinematic description important toward population research Description of tibiofemoral kinematics is less sensitive to anatomical variation than patellofemoral kinematics Abstract: Accurate assessment of knee kinematics is important to investigate knee pathology and the effect of orthopaedic interventions. Anatomical coordinate systems are used to describe knee kinematics but inherently show interpersonal differences. The purpose of this study was to determine the sensitivity of an anatomical coordinate system of the knee to anatomical variation, and to establish its effect on the description of knee kinematics. A statistical shape model of the knee was made based on a CT dataset. The statistical shape model was used to generate shapes with a specific variation. A coordinate system was calculated and the rotations relative to a mean coordinate system were calculated. From a dynamic CT dataset, knee kinematics were calculated for a flexion-extension movement. The largest rotational changes of the coordinate systems were then applied to the knee kinematics. The femoral and tibial coordinate system were relatively insensitive to anatomical variation, while the patellar coordinate system showed a larger sensitivity. Hence, tibiofemoral kinematics could be calculated with an accuracy of <5.01°, while patellofemoral kinematics showed a noticeably larger range of uncertainty (<13.48°). The findings from this study can be used to investigate whether differences in knee kinematics are due to anatomy or pathology.